The Socio-Political System of Yugoslavia as the Systemic Cause of its Collapse - Bazić, Jovan R. (Sociološki pregled, 2019)
The causes that inﬂuenced the disintegration of Yugoslavia are numerous. They are attributed various signifcance in the literature, but this paper devotes special attention to the socio-political regulation of the country, seen as the systemic cause of its disintegration. As early as during the creation process of the Yugoslav state, there were misunderstandings over the issue of its regulation, which would later generate political crises and encourage various ideas about the reorganization of Yugoslavia and its demise. This issue continually provoked conﬂicts in the country and the Yugoslav political emigration, which especially came to the forefront afer Tito’s death in times of a great socio-political and economic crisis in the country. These were favorable circumstances for the breakdown of Yugoslavia, in which international actors played a decisive role.